2021
DOI: 10.3991/ijep.v11i3.16505
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning During Pandemic Covid-19 Era: Drill Versus Conventional Models

Abstract: Coronavirus Disease 2019 (COVID-19) has been stated by the World Health Organization (WHO) as a pandemic. As a consequence, all teaching and learning processes have been conducted through e-learning. For that reason, this research aims at testing the computer-based drill learning and the conventional learning model through e-learning. The aspect that would be measured is the students’ mathematical reflecting thinking. The research method was the quasi-experimental by employing the pre-test, before the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…At the same time, the results of the experiment differ slightly for the identical experimental and control groups. Thus, the development and implementation of a model of professional foreign language training for future philology bachelors involving the use of online courses in Moodle is relevant to previous research [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the results of the experiment differ slightly for the identical experimental and control groups. Thus, the development and implementation of a model of professional foreign language training for future philology bachelors involving the use of online courses in Moodle is relevant to previous research [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that students believe online learning has increased their motivation and made them more engaged with the course content, and that online lectures were more organized than traditional face-to-face lectures. Students also revealed that online teaching had greater availability of resources which provided them with a better understanding of the course content [3,4,5]. Because of the greater availability of resources, students also noted that online study materials provide flexibility in the learning process and in general, save them time [7].…”
Section: Benefits Of Blended Learningmentioning
confidence: 99%
“…Traditionally in-person courses (face-to-face) had to swiftly switch the delivery mode to blended. Likewise, the pandemic forced schools around the world to shift from the traditional face-to-face classroom setting to a virtual or online setting, or even a blended learning environment that combines aspects of both [1][2][3]. It is only imperative that instructors review and identify important lessons that can be used to supplement future course deliveries.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, online learning (OL) was reserved for a particular group of learners: mostly older people with multiple family, work, financial and other responsibilities. These students benefited from the opportunities offered by this type of educational modality compared to traditional face-to-face education [1,2]. Expectations for the design and implementation of comprehensive online university education programs have been held back for a long time in a number of countries due to the prevalence and preference for face-to-face learning (FFL) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on several previous works related to online learning (OL), an instrument (questionnaire) was developed and implemented with the participation of 117 students. The research is quantitative-descriptive and had the following specific objectives: (1) To determine the attitude of university students towards EOL; (2) To characterize the learning experience of students in online modality; (3) To know about the available resources of students for EOL; and (4) To validate the developed questionnaire through a factor structure analysis. In general, the results show that students are proficient in the aspects related to selfmanagement of learning, but have a low level of motivation for EOL and suffer a deficit in aspects related to interaction with others (teachers and peers).…”
Section: Introductionmentioning
confidence: 99%